Problems Connected with Teaching Georgian - Loladze, Nana (Actual Problems of Kartvelology, 2013)
The team of Georgian language and literature at the National Examination Centre have conducted several tests for different purposes since 2000: examination of pupils of the 9th form (2000-2003), united national examinations (obligatory examinations in Georgian language and literature and an optional exam in literature), teacher certification examinations and graduate record examinations, national educational Olympiad for the 9th and 12th-grade pupils. Besides, preliminary written tests were conducted across the whole country. Analytic and qualitative research of the results enable us to monitor the teaching process, to identify gaps which will enable us to find out what changes and refinement can develop the existing teaching process. Quite sufficient time has passed since the school reform in order to evaluate it. Positive trends are evident but there are also problems connected with teaching Georgian language and literature. We should mention particularly the problems associated with teaching Georgian language ‘as Georgian is not just one of the subjects, but unlike other subjects, it is the language of teaching other subjects as well’ (National Teaching Plan)… The research has revealed that the existing national teaching plan requires serious changes. It is necessary to create united conception of teaching Georgian language for all three levels of education. More active involvement of linguists and their collaboration with pedagogical society.